1985
DOI: 10.1083/jcb.101.5.1903
|View full text |Cite
|
Sign up to set email alerts
|

A nucleus-basal body connector in Chlamydomonas reinhardtii that may function in basal body localization or segregation.

Abstract: We have isolated a nucleus-basal body complex from Chlamydomonas reinhardtii.The complex is strongly immunoreactive to an antibody generated against a major protein constituent of isolated Tetraselmis striata flagellar roots (Salisbury, J. L., A. Baron, B. Surek, and M. Melkonian, J. Cell Biol.,. Electrophoretic and immunoelectrophoretic analysis indicates that, like the Tetraselmis protein, the Chlamydomonas antigen consists of two acidic isoforms of ~20 kD. Indirect immunofluorescent staining of nucleus-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(180 citation statements)
references
References 43 publications
(37 reference statements)
10
169
0
1
Order By: Relevance
“…The DF contains centrin, also found in nuclear basal body connectors (NBBCs) (Fig. 1B), which are involved in localization of BBs during cell division (37). The two BBs have an identical structure of nine triplet microtubules that form a cartwheel arrangement (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DF contains centrin, also found in nuclear basal body connectors (NBBCs) (Fig. 1B), which are involved in localization of BBs during cell division (37). The two BBs have an identical structure of nine triplet microtubules that form a cartwheel arrangement (38).…”
Section: Resultsmentioning
confidence: 99%
“…In CR, robust NBBCs descending near the DF link BBs to the nucleus (Fig. 1B), and remain intact even after detergent lysis treatment (37). These can be induced by calcium to undergo significant contraction (69).…”
Section: Discussionmentioning
confidence: 99%
“…RNAi ablation of tubulin does not prevent 118 polarity establishment and is not required for centriole-cortex interaction [7,29], suggesting 119 that another cytoskeletal polymer mediates centriole position. However, another study found 120 that tubulin disruption delays polarity induction, which requires a small centrosomal 121 microtubule aster [30]; therefore the precise role of microtubules in this process remains to be 122 by centrin-containing rhizoplasts [61]. Is the nucleus, the centriole or both involved in the 209 movement to and from the apical surface?…”
Section: Actin In Centrosome/centriole Movements 111mentioning
confidence: 99%
“…Additional centrin-containing fibers descend from the basal bodies toward the nucleus ending in fimbrae that drape around the nucleus. NFAps were obtained by lysis of whole cells with nonionic detergent (Wright et al, 1985). A DIC image of the NFAp depicted in Figure 6H shows a successful extraction of cytoplasmic components.…”
Section: The Uni2 Protein Localizes To Basal Bodies and Probasal Bodiesmentioning
confidence: 99%
“…Indirect immunofluorescence in whole cells and nucleoflagellar apparatuses (NFAps) was conducted as described by Silflow et al (2001) based on methods described in Sanders and Salisbury (1995) and Wright et al (1985) with the following modifications. The rat anti-HA (3F10) high-affinity antibody (Roche Molecular Biochemical) was used at a 1:200 dilution and detected using a 488-conjugated goat anti-rat secondary antibody (Sigma Aldrich) at a 1:400 dilution.…”
Section: Indirect Immunofluorescence Labelingmentioning
confidence: 99%